Cryptosporidiosis in infancy and childhood mortality in Guinea Bissau, west Africa. Issue 6901 (14th August 1993) - Mølbak, K; Højlyng, N; Gottschau, A; Sá, J C; Ingholt, L; da Silva, A P; Aaby, P
Abstract : OBJECTIVE--To investigate the epidemiology of and mortality from cryptosporidiosis in young children in Guinea Bissau, West Africa. DESIGN--Three year community study of an open cohort followed up weekly. SETTING--301 randomly selected houses in a semi-urban area in the capital, Bissau. SUBJECTS--1315 children aged less than 4 years. MAIN OUTCOME MEASURES--Cryptosporidium infection detected by examination of stools during episode of diarrhoea and death of a child. RESULTS--Cryptosporidium spp were found in 239 (7.4%) out of 3215 episodes of diarrhoea. The parasite was most common in younger children (median age 12 months) and at the beginning of the rainy seasons. The prevalence of cryptosporidiosis was 15% (77/513) in cases of persistent diarrhoea compared with 6.1% (148/2428) in diarrhoea lasting less than two weeks (p < 0.0001). Cryptosporidiosis was associated with excess mortality in children who had the infection in infancy, and this excess mortality persisted into the second year of life (relative mortality 2.9 (95% confidence interval 1.7 to 4.9)). The excess mortality could not be explained by malnutrition, or by socioeconomic factors, hygienic conditions, or breast feeding. CONCLUSIONS--Cryptosporidiosis is an important cause of death in otherwise healthy children in developing countries.